Profil Miskonsepsi Mahasiswa Calon Guru Fisika Ditinjau Dari Berbagai Representasi Pada Materi Gerak Lurus Dan Gerak Parabola - Ahmad Busyairi; Muhammad Zuhdi (Department of Physics Education, Universitas Mataram, 2020)
Misconceptions are one of the problems that often occur in education. This objected aims to identify misconceptions of pre-service physics teachersÃ¢â¬â¢ in motion concept from various representations. The method used in this research is descriptive method. A total of 40 pre-service physics teachersÃ¢â¬â¢ at a university in the city of Mataram were involved in this study. The instrument used in the study was a three tier test with open reasons. The reasons have been made to be open aims so that pre-service physics teachersÃ¢â¬â¢ are more free to describe the understanding that is in their cognitive structure. A total of 15 test items used in this study. The questions are classified into three types of representations namely; verbal, vigural, and graphics. The results showed that 67% of pre-service physics teachers have misconceptions on the concept of linier motion, 53% of misconceptions on the concept of vertical motion, and 57% of misconceptions on the concept of parabolic motion. The result shows that 61% of pre-service physics teachersÃ¢â¬â¢ have misconceptions on verbal type questions, 59% of misconceptions on vigural type , and 61% misconceptions on graphic type.